Optimizing the pole properties in Pole Vaulting by using genetic algorithm based on frequency analysis - Jahromi, A. F.; Atia, A.; Bhat, R. B.; Xie, W.-F. (International Journal of Sports Science and Engineering, 2012)
The pole vaulting is a sport with a long history involving complex dynamic motion. The aim of pole vaulting for the athlete is to achieve maximum height. The dynamic behavior of the pole-athlete system is identical to an inverted pendulum system with the buckling pole acting as a spring. The purpose of this paper is to study the influence of factors on the pole vaulting performance such as the initial velocity of the athlete, pole stiffness and length. The best results are obtained when all the stored potential energy in the pole is released with the pole reaching the 90 degrees condition for success. The natural frequency of the poleathlete system is obtained by Fast Fourier Transform (FFT). The storing and releasing time of potential energy should be equal to half the natural period. Based on this condition the pole length and stiffness are determined by using Genetic Algorithm (GA) so as to achieve maximum height. This paper presents an optimization procedure to design a flexible pole based on the frequency analysis. The result of this research can be utilized in sport industries to design optimum poles.